2014
DOI: 10.3758/s13423-014-0621-6
|View full text |Cite
|
Sign up to set email alerts
|

How is letter position coding attained in scripts with position-dependent allography?

Abstract: We examined how letter position coding is achieved in a script (Arabic) in which the different letter forms (i.e., allographs) may vary depending on their position within the letter string (e.g., compare the same-ligation pair [see text] and [see text] vs. the different-ligation pair [see text] and [see text]. To that end, we conducted an experiment in Uyghur, an agglutinative language from the Turkic family that employs an Arabic-based script in which both consonants and vowels are explicitly written. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 22 publications
8
12
0
1
Order By: Relevance
“…This difference was not due to any potential peculiarities of the prime-target stimuli because a replication of the experiment with intermediate adult learners of Arabic (who did not know most of the words) revealed a transposed-letter priming effect regardless of the order of the root letters. Perea et al concluded that "the masked priming samedifferent task may be sensitive to factors above the level of letter representations" (p. 916; note, however, that Kinoshita et al, 2012, argued that these results reflected a confound with position-dependent allography; see Yakup, Abliz, Sereno, & Perea, 2014, for empirical evidence for a role of position-dependent allography in Arabic script).…”
mentioning
confidence: 99%
“…This difference was not due to any potential peculiarities of the prime-target stimuli because a replication of the experiment with intermediate adult learners of Arabic (who did not know most of the words) revealed a transposed-letter priming effect regardless of the order of the root letters. Perea et al concluded that "the masked priming samedifferent task may be sensitive to factors above the level of letter representations" (p. 916; note, however, that Kinoshita et al, 2012, argued that these results reflected a confound with position-dependent allography; see Yakup, Abliz, Sereno, & Perea, 2014, for empirical evidence for a role of position-dependent allography in Arabic script).…”
mentioning
confidence: 99%
“…Unfortunately, neither the naming task used by Friedmann and Haddad-Hanna (2012) with impaired individuals nor the RSVP task used by Yakup et al (2014) can inform the temporal locus of the obtained effects. The goal of the present experiments was to examine the impact of the ligation pattern on letter identity/ position during the early stages of visual-word recognition in an Arabic-Persian script (Uyghur).…”
mentioning
confidence: 99%
“…It has been pointed out in mono‐linguistic studies of adult readers that specific characteristics of the orthography affect the size (or even the presence) of the TL effect (e.g. the subsyllabic structure of the Korean hangul script, see Lee & Taft, , ; the position‐dependent allography of the Arabic‐based Uyghur script, see Yakup, Abliz, Sereno & Perea, ; the distribution of transitional probabilities of root‐derived words in Semitic languages, see Perea, Gatt, Moret‐Tatay & Fabri, ). These results clearly support the view that between‐orthography differences do modulate the optimal manner of lexical access, and the orthographic system adapts to these differences even at the level of position encoding.…”
Section: Discussionmentioning
confidence: 99%